International or Global—The Expanding Universe of Librarianship - Rudasill, Lynne M (Portal (Baltimore, Md.), 2009)
This year, the United States Department of Education Title VI programs will celebrate their 50th anniversary. During the Cold War, the United States government passed the National Defense Education Act to marshal all possible resources to improve education in multiple subject areas, initiating the development of National Research Centers (NRCs) in universities across the country, in addition to supporting the race to the moon. Focusing on various geographic regions, including Africa, Asia, and Latin America, these centers were funded to provide support for scholars working in the language, literature, and cultures of countries around the world, with special emphasis on the vernacular languages. The overarching purpose was the enhancement of American understanding of areas outside of the borders. One of the key factors for any university receiving these grants has always been the existence of library resources that will support scholarship in the respective areas. The NRC is in many ways the foundation for area studies librarianship. This article discusses the growing interest in international librarianship. An increasing number of library schools are offering courses related to "international" or "global studies" librarianship. This type of librarianship is not just about a desire to travel to interesting and even exotic places. It implies a real concern about how information is shared, developed, collected, and controlled. The author offers some caveats for those interested in this type of librarianship and discusses the future of global and area studies. (Contains 3 notes.)